Perceptions of principals and teachers towards the implementation of the revised secondary education program in Zamboanga City - Ko, Bernabela L. 1926- (1975)
The subjects, 385 teachers and 14 principals from 4 public and 8 private secondary shools, answered questionnaires and were interviewed for their perceptions of problems in implementing the Revised Secondary Education Program of 1973. On the curriculum content and strategies, teachers and principals agreed that the program makes the students more civic-minded and concerned with the welfare of the community and that the new curriculum implements objectives and goals of the New Society. However, instructional materials such as textbooks, tools, and other facilities are inadequate and the program allows a limited choice of electives. Demonstration teaching, seminars, work shops and work conferences of the teachers are needed to solve implementation problems.
Thesis (M.Ed.)--University of the Philippines
Keywords: Education, Secondary; Educators -- Philippines